"The cuts, they trimmed the people" – School children, precarity and European citizenship. (November 2016) - Richardson, Mary
Recently, the Education, Audiovisual and Culture Executive Agency (2012) have funded programmes designed to advance European citizenship and citizen competences through education. This paper reports on the findings from one project, Creative Connections, designed to encourage the "voices" of young people in exploring European identities. Children (aged 9–16) in 25 schools in six European Union (EU) countries (UK, Finland, Spain, Czech Republic, Portugal and Ireland) developed artworks that explored perceptions of European citizenship. Their art was posted on a secure website and they discussed images with peers using automatic online translated blogs. The project facilitated representations of identity/belonging using a range of media. However, some artworks suggested that children were alienated from "Europe", particularly EU responses to global austerity. This paper uses the theory of precarity to examine the ways in which the children expressed their concerns. Some artworks suggest that recent economic and political decisions have had the effect of challenging a sense of shared European citizenship; they resist a positive sense of identification with Europe and demonstrate fear for their future based on their current lives. This indicates that the EU's educational goals to promote citizenship competences may require revision to account for the challenges of contemporary societies.